ПАЛЕООЗЕРНЫЕ ВОДОЕМЫ БОЛЬШОГО КАВКАЗА И НЕПАЛЬСКИХ ГИМАЛАЕВ: РАСПРОСТРАНЕНИЕ И ГЕНЕТИЧЕСКИЕ ОСОБЕННОСТИ - Ефремов Ю.В.; Салпагаров Д.С.; Зимницкий А.В. (My University, 2005)
The distribution of the paleolake basins in mountain areas is analyzed. The description of the genetic features of the lake basin deposits is given. Authors suggest distinguishing the lake period in the history of mountain areas.
Keywords: 551.4.07(234.9+235.243)